Collagen fingerprinting for the species identification of archaeological amphibian remains. (20th May 2020) - Buckley, Michael; Cheylan, Marc
Abstract : Amphibians are well known as being one of the main groups of animals today most threatened by environmental changes but they are also some of the least well understood of all terrestrial vertebrates. This gap in knowledge is much greater as we look further back into the relatively recent past, despite representing an invaluable resources in archaeological and palaeontological assemblages that are more indicative of palaeoclimate conditions than most other vertebrate taxa. This in part stems from their remains being typically much less studied, partly due to the less common forms of expertise required for identifications based on skeletal morphology – the most frequently observed tissue that remains in ancient assemblages. Here we apply a method of biomolecular species identification by collagen peptide mass fingerprinting to the British Late Pleistocene assemblage of Pin Hole Cave (Creswell Crags, UK) as well as a range of relevant extant taxa for comparison. Our results demonstrate the ability to separate at the species level with all modern taxa investigated, allowing for the identification of these archaeological remains to the amphibian taxa known to exist in Late Pleistocene Britain. Analyses of the Pin Hole assemblage found a dominance of the two species previously known from the site (common frogs and toads: Rana temporaria and Bufo bufo, respectively) and also a small number of the rarer natterjack toad ( Epidalea calamita ) not previously identified in the Creswell Crags region but known from other sites in the UK; additionally, one specimen appeared to yield the fingerprint of the moor frog ( R. arvalis ), now extinct in the UK. As such, collagen fingerprinting is here shown to widen the known palaeobiodiversity of taxa, and highlights the further potential to enhance our understanding of climate change in the past.